Floristic Variation of Tree Communities In Island Forests of Pulau Tuba and Gunung Raya Forest Reserve, Langkawi - Pardi, F; N Mohd Said, M; Ismail, A; J Sidik, N; A Radzun, K; S Ishak, N (International Journal of Engineering and Technology, 2019)
Island forests are among forest habitats that are vulnerable to natural and anthropogenic disturbances, whereby the disturbances would influence the survival of biological species of the ecosystems. Langkawi Archipelago contains many small island forests and rapid development of tourism industry within this archipelago might contribute impacts to the tree flora of the forest communities on the small islands. Hence, in this study the species richness and floristic variation pattern of tree communities of two selected island forests in the Langkawi Archipelago were explored, and data gathered are anticipated to be used for management of island forests in Langkawi. Tree survey was carried out in 10 study plots of 20m x 25m each, at island forests of Pulau Tuba Forest Reserve (PTB) and Gunung Raya Forest Reserve (GRFR), making the total of 20 study plots. All trees with diameter at breast height (dbh) of 5.0 cm and above were enumerated and tree species were identified. Species data were analyzed for diversity and richness using the Shannon and Margalef indices; whilst Detrended Correspondence Analysis (DCA) was used to determine floristic pattern. A total of 1062 trees were recorded from all study plots which comprised of 49 families, 134 genera and 213 tree species. The GRFR exhibited the highest species number of 135 tree species, followed by the PTB (106 tree species). Species accumulation curves showed that the curves were far from reaching the asymptote even when the whole dataset were combined. The DCA ordination diagram clearly grouped the study plots by their geological formation that indicated a gradient of species change in GRFR and PTB sites.Â Â